2023
DOI: 10.1002/smtd.202301325
|View full text |Cite
|
Sign up to set email alerts
|

Nested Biofabrication: Matryoshka‐Inspired Intra‐Embedded Bioprinting

Mecit Altan Alioglu,
Yasar Ozer Yilmaz,
Yogendra Pratap Singh
et al.

Abstract: Engineering functional tissues and organs remains a fundamental pursuit in bio‐fabrication. However, the accurate constitution of complex shapes and internal anatomical features of specific organs, including their intricate blood vessels and nerves, remains a significant challenge. Inspired by the Matryoshka doll, here a new method called “Intra‐Embedded Bioprinting (IEB)” is introduced building upon existing embedded bioprinting methods. a xanthan gum‐based material is used which served a dual role as both a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Intervertebral discs and multilayer gradient scaffolds were also constructed ( Figure 7C ). Alioglu et al [ 118 ] reported a Matryoshka-inspired intra-embedded bioprinting method to develop nested bioprinted models by demonstrating embedded bioprinting inside pre-existing embedded bioprinted structures. Moxon et al [ 119 ] bioprinted anisotropic osteochondral implants with distinct mechanical properties ( Figure 7D ).…”
Section: Embedded Bioprinting Of 3d Complex Structuresmentioning
confidence: 99%
“…Intervertebral discs and multilayer gradient scaffolds were also constructed ( Figure 7C ). Alioglu et al [ 118 ] reported a Matryoshka-inspired intra-embedded bioprinting method to develop nested bioprinted models by demonstrating embedded bioprinting inside pre-existing embedded bioprinted structures. Moxon et al [ 119 ] bioprinted anisotropic osteochondral implants with distinct mechanical properties ( Figure 7D ).…”
Section: Embedded Bioprinting Of 3d Complex Structuresmentioning
confidence: 99%